Climate trauma : foreseeing the future in dystopian film and fiction - Kaplan, E. Ann (Rutgers University Press, 2016)
Examining a variety of films that imagine a catastrophic future, from Children of Men to The Book of Eli, E. Ann Kaplan considers how they have exacerbated our sense of impending dread, triggering what she terms "Pretraumatic Stress Disorder." But Climate Trauma also explores ways these films might help us productively engage with our anxieties about climate change, giving us a prophetic glimpse of the terrifying future selves we might still work to avoid becoming.